Pengembangan Instrumen Tes Higher Order Thinking Skills (HOTS) Pada Mata Pelajaran Sejarah Indonesia - Amelia Rahman; Ofianto Ofianto; Ridho Bayu Yetferson (PAKAR Pendidikan, 2019)
This research was motivated because of the revisions in the 2013 curriculum, which was one of in the assessment of learning outcomes. In order to improve students' thinking skills, the ability to think higher (HOTS) are needded. Based on the results of observations in the field in making test instruments for Higher Order Thinking Skills (HOTS) in the Indonesian history subjects teachers still experience obstacles in making them, so that there is a lack of instruments that can evaluate and measure students' abilities. This study aims to develop appropriate and practical test instruments Higher Order Thinking Skills (HOTS) used by teachers and students in the assessment of learning outcomes. This research is a method of research and development, using the ADDIE model which consists of 5 stages, namely analysis, planning, development, implementation and evaluation. Because of the limited time researchers only reach the implementation stage. The subjects of this study were tested for validity and practicality based on evaluations from evaluation experts, history subject’s teachers and students using questionnaires to assess the appropriateness and practicality of the instrument. The results of the study show that the feasibility of the test instruments for Higher Order Thinking Skills (HOTS) is based on the evaluation of expert evaluations was 4.04, indicating that it is very feasible to use. As for the practicality testing by teachers and students, the average score was 3.87 and 4.10 showed that the test instruments of the Higher Order Thinking Skills (HOTS) were practically used.